A comparative evaluation of ideal apical sealing material for open apex single rooted permanent tooth: An in vitro study - Chiranjit Ghosh; Gautam Kumar Kundu; Shabnam Zahir; Subrata Sarkar; Badruddin Ahmed Bazmi; Sudipta Kar (Wolters Kluwer Medknow Publications, 2015)
Introduction: Traumatic injury and dental caries in developing tooth can cause irreversible damage to the pulpal tissue, which hinders the normal physiologic root development. Aims and Objectives: The aim was to find out the sealing efficacy of mineral trioxide aggregate (MTA) as an ideal apexification material of a permanent tooth with an open apex by comparative evaluation of grey and white MTA of different thickness and time interval in vitro. Materials and Methods: A total of 144 teeth were randomly distributed into 6 equal test groups containing 24 teeth each and then filled with white and gray MTA to thickness of 1, 2, and 4 mm. Microleakage of these samples was studied by bacterial leakage model at definite intervals (After 24 h,7 th day,15 th day, and 30 th day). Results: After 24 h, for 1 mm thickness, grey MTA showed less leakage than white MTA, but the difference is not statistically significant at 5% level (Z = 0.32, P = 0.75). After 7 days, in 1 and 2 mm thickness, White MTA showed 64.71% and 16.67% leakage, while Grey MTA revealed 50% and 8.33% leakage in the same category. No leakage was found among the samples of 4 mm in both MTA. After 15 days in 1 mm, 100% leakage was recorded in both MTA. In 2 mm, presence of leakage is 15% for White and 13.64% leakage were present in Grey MTA. However, this difference is not significant (Z = 0.126, P = 0.9). In 4 mm MTA, only 1 leakage was found in White and none for Grey. This difference is not significant (Z = 1.02, P = 0.31). After 30 days, in 2 mm, 9% more leakage was observed in White MTA samples (23.53%) than that of Grey MTA (14.29%). In the category of 4 mm, 0.37% more leakage was observed in White MTA samples (8.70%) than that of Grey MTA (8.33%). However, this difference was not statistically significant. Conclusion: The present study showed that apical barrier of 4 mm demonstrated less leakage than 1 and 2 mm barrier in both White and grey MTA after 30 days of study and grey MTA demonstrated significantly less leakage than white MTA.